2012
DOI: 10.1007/s00267-012-9949-8
|View full text |Cite
|
Sign up to set email alerts
|

Trying Not to Get Burned: Understanding Homeowners’ Wildfire Risk–Mitigation Behaviors

Abstract: Three causes have been identified for the spiraling cost of wildfire suppression in the United States: climate change, fuel accumulation from past wildfire suppression, and development in fire-prone areas. Because little is likely to be performed to halt the effects of climate on wildfire risk, and because fuel-management budgets cannot keep pace with fuel accumulation let alone reverse it, changing the behaviors of existing and potential homeowners in fire-prone areas is the most promising approach to decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(91 citation statements)
references
References 33 publications
4
81
1
Order By: Relevance
“…This supports earlier work by Dickinson et al (2015) that suggested receiving fire-related information from "experts" was positively associated with both structural and vegetation mitigation behaviors. Others have found similar relationships between fire-related information sources and mitigation behavior (Hall and Slothower 2009, Brenkert-Smith et al 2012, while one team found that simply being familiar with http://www.ecologyandsociety.org/vol22/iss1/art21/ the Community Wildfire Protection Plan was enough to increase the likelihood of completing mitigation actions (Wolters et al, personal communication).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…This supports earlier work by Dickinson et al (2015) that suggested receiving fire-related information from "experts" was positively associated with both structural and vegetation mitigation behaviors. Others have found similar relationships between fire-related information sources and mitigation behavior (Hall and Slothower 2009, Brenkert-Smith et al 2012, while one team found that simply being familiar with http://www.ecologyandsociety.org/vol22/iss1/art21/ the Community Wildfire Protection Plan was enough to increase the likelihood of completing mitigation actions (Wolters et al, personal communication).…”
Section: Discussionmentioning
confidence: 93%
“…We received 532 responses, for a response rate of 31%. This response rate is in line with recent randomly sampled survey projects on wildfire topics (e.g., Kyle et al 2010, Brenkert-Smith et al 2012, McNeill et al 2013. To explore possible responder bias, we compared demographic variables from our sample to those from the three surveyed counties using U.S. Census Bureau (2015) facts.…”
Section: Survey Of Homeownersmentioning
confidence: 85%
See 1 more Smart Citation
“…Although many conceptual frameworks of risk mitigation behaviour incorporate variables representing people's perceptions of their ability to mitigate a risk (e.g. self-efficacy) (Brenkert-Smith et al 2012), the combination of variables that represent capacity in our study arguably do so from more of an objective standpoint.…”
Section: Discussionmentioning
confidence: 99%
“…As such, research on the social system tends to be parsed into broad efforts to articulate the policy approaches that undergird the wildland fire dilemma (Steelman and Burke 2007) or more specific research efforts that identify behavioral response. Research on behavioral response generally focuses on shorter term coping behaviors before, during, and after stages of the disaster cycle, and includes mitigation activities and determinants of such hazard-related behaviors before an event (e.g., structural improvements, vegetation reduction around the home) (Martin et al 2009, Brenkert-Smith et al 2012, Dickinson et al 2015 and preparedness activities and their determinants (e.g., evacuation planning) (Cohn et al 2006, Jakes et al 2007, Paveglio et al 2010. And finally, limited work examines factors that influence the trajectories of recovery and likelihood of rebuilding after a disaster (Mockrin et al 2015) that may contribute to a shift from coping to adaptation.…”
Section: Fire Adaptationmentioning
confidence: 99%